Epithelial-Mesenchymal Transition Drives Three-Dimensional Morphogenesis in Mammalian Early Development - Ismagulov, Galym (Front Cell Dev Biol, 2021)
From fertilization to onset of gastrulation, a mammalian embryo goes through several rounds of cellular morphogenesis resembling phenomena of epithelial-mesenchymal transition (EMT) and mesenchymal-epithelial transition (MET), collectively referred to as EMTs. How these EMT events play a role in shaping the three-dimensional (3-D) architecture of the developing embryo is not well-understood. In this review, we present a model in which cellular morphogenesis, represented primarily by dynamic changes in its epithelialization status, is the driving force of embryonic 3-D organization. This is achieved through the integration of three key components of mammalian early development, the pluripotency regulation, morphogenetic signaling, and biomechanical force anisotropy. Although cells in an early embryo do not exhibit full mesenchymal characteristics, our model underscores the importance of investigating molecular regulation of epithelial cell polarity and partial EMT/MET in understanding mammalian early development.